Beloved eaudiobook - Morrison, Toni (Random House Audio, 2006)
PULITZER PRIZE WINNER • NEW YORK TIMES BESTSELLER • A spellbinding novel that transforms history into a story as powerful as Exodus and as intimate as a lullaby. With a new afterword by the author.  This "brutally powerful, mesmerizing story” ( People) is an unflinchingly look into the abyss of slavery, from the acclaimed Nobel Prize winner. Sethe was born a slave and escaped to Ohio, but eighteen years later she is still not free. Sethe has too many memories of Sweet Home, the beautiful farm where so many hideous things happened. And Sethe’s new home is haunted by the ghost of her baby, who died nameless and whose tombstone is engraved with a single word: Beloved.  “A masterwork.... Wonderful.... I can’t imagine American literature without it.” —John Leonard, Los Angeles Times